New scandals – time to rethink the rules? (Italian original version) - Pietro Greco (JCOM: Journal of Science Communication, 2006)
The scandal of the “biotechnology evangelist” erupted in Korea at the beginning of the new year: a commission from Seoul National University announced that it had proof that Dr Woo Suk Hwang, considered one of the world’s foremost experts on cloning by nucleus transfer, had manipulated the data concerning experiments in human cell cloning and the creation of eleven lines of stem cells from human embryos published in two different articles in the journal Science in 2004 and 2005.